Combined Spraying of Boron and Zinc During Fruit Set and Premature Stage Improves Yield and Fruit Quality of European Hazelnut cv. Tonda di Giffoni - Meriño-Gergichevich, Cristian; Luengo-Escobar, Ana; Alarcón, David; Reyes-Díaz, Marjorie; Ondrasek, Gabrijel; Morina, Filis; Ogass, Khristopher (Frontiers in Plant Science, 2021)
Boron and Zn are essential micronutrients of plant nutrition programs in orchards for securing the crop quality and yield. Although orchard supplementation with B and Zn are a common practice to overcome deficiencies or maintaining their optimal levels, the efficiency of combined B and Zn spraying in relation to European hazelnut (Corylus avellana L.) phenological stage has not been investigated so far. Leaf and kernel mineral and functional traits were studied in cultivar Tonda di Giffoni after B and Zn spraying in four phenological stages. During the 2016/17 season, nine-year-old trees were sprayed with B (0, 800 and 1600 mg L-1) and Zn (0, 400 and 800 mg L-1) under three treatments: B0+Zn0, B800+Zn400 and B1600+Zn800 implemented in three spring application programs scheduled from October to December (P1: four times, P2: early two times and, P3: late two times). B and Zn treatments in P1 and P3 led to higher Zn concentration both in leaves and kernels compared to non-sprayed trees. Stabilized nut production increased 2.5-folds under B800+Zn400 in all three programs. Kernel/nut ratio improved in both B+Zn treatments in P1 and P3, while the percentage of blank nuts were reduced compared to B0+Zn0. Increased radical scavenging activity in B+Zn-treated kernels and leaves was not attributed to phenolics accumulation in P3 compared to B0+Zn0, whereas B and Zn spraying reduced the level of lipid peroxidation in both studied organs. According to the results, combined B and Zn should be sprayed at the end of spring (P3) on hazelnut plantation in temperate areas as Southern Chile, whereas early applications (P2) showed an irregularity in nut production and functional traits in nuts. Moderate and partialized rates of B and Zn and the time of implementation contribute to improving the quantitative and qualitative features crucial for future sustainable hazelnut production.